Application of matrix equations in the AIDA method - Michał Wiśniewski (Foundations of Management, 2019)
The article presents the problem of a decision-making process based on the method known as the analysis of interconnected decision areas (AIDA). Author described the basic assumptions of the AIDA method and the classic method of its implementation with the usage of a decision tree. Crucially, the new and innovative improvement in development of the AIDA method is connected with the replacement of the decision tree by the matrix equation to speed up the cost assessment of decision variants.
Keywords: C10; H12; 650; decision-making; decisive problem; matrix; decision area; elementary decision; decision trees